Effect of Osmosis Time and Sucrose Concentration on The Antioxidant Activity of Red Dragon Fruit Juice (Hylocereus polyrhizus) : Efek Lama Osmosis dan Konsentrasi Sukrosa Terhadap Aktivitas Antioksidan (DPPH) Sari Buah Naga Merah (Hylocereus polyrhizus) - Azizah, Idha Noer; Budiandari, Rahmah Utami; WDP, Al Machfudz (Universitas Muhammadiyah Sidoarjo, 2023)
Dragon fruit contains antioxidants, beta-carotene, ascorbic acid and dietary fiber content in the form of pectin. Antioxidant are chemical compounds that can donate one or more electrons to free radicals to inhibit free radical reactions. Red dragon fruit can be processed into natural red dragon fruit juice using osmosis extraction. Osmotic extraction is done by soaking the fruits with sugar, it is done so that the water comes out towards the media. The advantages of osmosis are also many of them are easy, natural manufacture, the tools used are simple so that the fruit juice produced is safe for consumption by humans. The purpose of this study to determine the antioxidant activity of red dragon fruit juice. Antioxidant activity testing was carried out using the DPPH method (1,1 Diphenyl-2-picrylhydrazyl). This research was conducted using a factorial Randomized Block Design (RAK) with the first factor being sugar concentration which consisted of 3 treatment levels, namely (25%, 50% and 75%) and the second factor was osmosis duration (12, 24, and 36 hours). The results showed that red dragon fruit juice in the 24-hour 50% treatment had the highest antioxidant activity with an IC50 value of 28.